The use of mind mapping to improve writing skill of the eighth grade students of junior high school - Ni Kadek Herna Lastari; Putu Ritra Trees Ari Kartika Hadi Saraswati (Politeknik Negeri Bali, 2018)
There were some problems found in the eighth-grade students’ writing skill of SMP90-DB. The students, in general, did not know the way how to generate and organize their own ideas into well-formed work of writing. The researchers aimed to improve their writing skill and tried to investigate the effect of mind mapping in improving writing skill of the eighth-grade students of SMP90-DB. The objective of the study was to figure out whether or not writing skill of the eighth-grade students of SMP90-DB in academic year 2016/2017 could be improved through mind mapping. The participants were 35 students from VII-I class which covered 17 males and 18 females. The mean score of pre-test was 60.44 which implied that the writing skill of the participants was still low with none of the students passed the passing minimum score. The research was conducted in two cycles of the application of mind mapping. The data were collected from post-tests which were taken after applying mind mapping. The result indicates that 21 students passed the minimum score after post-test 1 and 33 students passed the minimum score after post-test 2. It can reveal that there is a significant improvement in the subjects’ writing skill after the implementation of mind mapping. Furthermore, the questionnaire results proved that the students’ responses to the implementation of mind mapping were positive. It could be concluded that mind mapping is an effective technique in improving writing skill of the eighth-grade students of SMP90-DB in academic year 2016/2017.